A cross-sectional study on vision-related quality of life in patients with ocular GvHD - Pezzotta, S; Rossi, G C; Scudeller, L; Antoniazzi, E; Bianchi, P E; Perotti, C; Del Fante, C (Bone marrow transplantation (Basingstoke), 2015)
Ocular GvHD affects about 40–60% of patients receiving bone marrow transplantation. Ocular complaints worsen quality of life (QoL), which, besides survival time, is a primary end point in a patient's follow-up. The aim of our study was to assess the ocular surface status and vision-related QoL (VRQoL) and explore the potential determinants in VRQoL in patients with chronic GvHD with ocular involvement. In this cross-sectional study, we investigated 40 patients with ocular GvHD after allogeneic hematopoietic stem cell transplantation assessing ocular symptoms and signs, VRQoL and ophthalmologic parameters. The median age was 52.1 years; 32.5% were females. Most of them presented a multiple organ involvement. Ophthalmological parameter examinations were on average abnormal. Corneal staining was severe/very severe in 25%; conjunctival staining in 10% of subjects. The worse QoL scores were on ‘general vision’, ‘ocular pain’, ‘vision-specific mental health’ and ‘vision-specific role difficulties’. Both symptoms and sign scores indicate poor VRQoL. A lower VRQoL was related to schooling level, job position, underlying disease and extracorporeal photopheresis. Corneal staining, Schirmer and tear film breakup time were negatively associated to visual function-related subscales. An accurate ophthalmological and VRQoL assessment should be mandatory for a long time to promptly recognize early signs of ocular suffering, and to prevent irreversible ocular complications.